Social support as predictors of reducing work stress on early childhood education teacher - Nadhirotul Laily; Abdul Muhid (Journal of Early Childhood Care and Education (JECCE), 2021)
A profession as a teacher and teaching activity are activities that often make people stressed. People who deal with stress effectively can reduce work stress if they get resources from the surrounding environment through social support. This study aims to test social support as a predictor to reduce work stress for Early Childhood Education (abbreviated ECE) teachers. This study uses a quantitative approach with a correlational causality design. The survey method used to collect data is by distributing instruments that had gone through the adaptation process. Convenience sampling was used to get 58 respondents. The research hypothesis is tested using simple linear regression analysis with SPSS Program for Windows Version 20. The result of statistical analyses presents that social support has a significant negative effect on stress at work. This research contributes to ECE teachers' social support and stress, where this topic is still limited to research.